Microstructures, mechanical properties and reliability induced from size effect in Sn-based solder joints: Review - Sijin Li; Xiaowei Wang; Mingqing Liao; Zezheng Li; Qi Li; Han Yan; Aidong Liu; Fengjiang Wang (Journal of Materials Research and Technology)
With the continuous advancement of integrated packaging technology, the dimensions of Sn-based interconnected joints are being steadily reduced. It is necessary to investigate the dependability of Sn-based solder joints with various size since the change in size influences the mechanical and microstructural characteristics of solder joints. This review summarized the influence of solder joint sizes on the microstructure, with a focus on intermetallic compound (IMC), element diffusion, and undercooling. Moreover, the mechanical properties and electromigration reliability of solder joints of varying sizes were also included. The thickness and grain size of interfacial IMC layer generally increased with the joint size decreasing, but were also dependent on joint structure, solder composition and substrate. Smaller solder sizes led to greater undercooling during β-Sn nucleation, subsequently influencing the grain size and orientation within the solder microstructure. The tensile or shear strength of solder joints increased with the decrease on joint size, while the effect on creep properties were summarized based on the formation from the bulk solder to solder joints. The change on bulk solder sizes or solder joint size would obviously affect the creep properties of solder or solder joints. Because the solder size in packaging structure falls precisely within the characteristic size range for electromigration, with solder joint size decreased to the critical length, electromigration-induced failure can be entirely eliminated, which would be beneficial for the design on solder joints for high current operation.